Putative virulence factors of Corynebacterium pseudotuberculosis FRC41: vaccine potential and protein expression - Santana-Jorge, Karina T. O.; Santos, Tulio M.; Tartaglia, Natayme R.; Aguiar, Edgar L.; Souza, Renata F. S.; Mariutti, Ricardo B. [UNESP]; Eberle, Raphael J. [UNESP]; Arni, Raghuvir K. [UNESP]; Portela, Ricardo W.; Meyer, Roberto; Azevedo, Vasco (Biomed Central Ltd, 2016)
Background: Corynebacterium pseudotuberculosis, a facultative intracellular bacterial pathogen, is the etiological agent of caseous lymphadenitis (CLA), an infectious disease that affects sheep and goats and it is responsible for significant economic losses. The disease is characterized mainly by bacteria-induced caseous necrosis in lymphatic glands. New vaccines are needed for reliable control and management of CLA. Thus, the putative virulence factors SpaC, SodC, NanH, and PknG from C. pseudotuberculosis FRC41 may represent new target proteins for vaccine development and pathogenicity studies. Results: SpaC, PknG and NanH presented better vaccine potential than SodC after in silico analyses. A total of 136 B and T cell epitopes were predicted from the four putative virulence factors. A cluster analysis was performed to evaluate the redundancy degree among the sequences of the predicted epitopes; 57 clusters were formed, most of them (34) were single clusters. Two clusters from PknG and one from SpaC grouped epitopes for B and T-cell (MHC I and II). These epitopes can thus potentially stimulate a complete immune response (humoral and cellular) against C. pseudotuberculosis. Several other clusters, including two from NanH, grouped B-cell epitopes with either MHC I or II epitopes. The four target proteins were expressed in Escherichia coli. A purification protocol was developed for PknG expression. Conclusions: In silico analyses show that the putative virulence factors SpaC, PknG and NanH present good potential for CLA vaccine development. Target proteins were successfully expressed in E. coli. A protocol for PknG purification is described.
Keywords: Corynebacterium pseudotuberculosis; Pathogenicity and virulence; Vaccine potential; Epitope prediction; Protein expression; Protein purification